Contemporary Studies on Asian Cities - Patrick Heinrich (International Quarterly for Asian Studies, 2020)
This review article explores recent urban studies in Asia in order to explore differences, similarities and convergences between urban and area studies. The review of three recent publications of urban studies in Asia is motivated by the transnational and transcultural make-up of many contemporary Asian cities and their growing interconnectivity. These phenomena result in a rescaling of urban economies and networks, and this is also reflected in urban ambitions and planning. After a brief presentation of the three publications under review, I discuss three questions: Why do urban studies matter for area studies? How are social relations articulated in urban spaces? What is the city doing to people and what are people doing to the city? The discussion of these questions notes that the relation between city, nation state, neighbouring states and the rest of the world has become more complex and harder to predict. Careful consideration of the cases under study reveals processes of a recalibration of relations, calling for the attention of area studies. Urban centres constitute a rewarding field of studies as they require a new focus on new details, experiences and developments.